Evaluation of the Effectiveness of Dose Individualization to Achieve Therapeutic Vancomycin Concentrations. (10th May 2018) - Abulfathi, Ahmed A.; Chirehwa, Maxwell; Rosenkranz, Bernd; Decloedt, Eric H.
Abstract: The glycopeptide antibiotic vancomycin is used for treatment of methicillin‐resistant Gram‐positive cocci. Adequate vancomycin plasma concentrations are related to bacterial cure. However, inter‐ and intrapatient variability make it difficult to achieve therapeutic vancomycin concentrations. The primary objective of this study was to determine the effectiveness of using computerized therapeutic drug monitoring (TDM) to assist in achieving therapeutic vancomycin concentrations at a tertiary hospital in South Africa. This was a 2‐period study consisting of a retrospective 1‐month observational period followed by a prospective 1‐month period in which computerized TDM was implemented as an intervention to assist with vancomycin dose individualization. During the prospective period, all vancomycin TDM results were followed by dosage individualization using computerized TDM. The retrospective period included 77 patients with 292 vancomycin concentrations: 69% (53/77) adult and 31% (24/77) pediatric patients. The prospective period included 80 patients with 217 vancomycin concentrations measured: 69% (55/80) adult and 31% (25/80) pediatric patients. Fewer vancomycin TDM data were requested during the prospective period with a median (interquartile range) of 2 (1–3) samples per patient compared with 3 (1–5) samples per patient during the retrospective period. The odds ratio of achieving therapeutic trough concentrations was 3.63 (95%CI 1.81–7.3) in the prospective period when TDM‐adjusted vancomycin dosing and appropriate TDM procedures were applied. The use of computerized TDM resulted in a higher frequency of therapeutic vancomycin concentrations in a middle‐income setting. Trough vancomycin concentrations alone correlate poorly with the area under plasma concentration‐time curve from 0 to 24 hours.